2009
DOI: 10.1007/s10549-009-0488-9
|View full text |Cite
|
Sign up to set email alerts
|

Three common TP53 polymorphisms in susceptibility to breast cancer, evidence from meta-analysis

Abstract: The association of polymorphisms of tumor suppressor gene TP53 with breast cancer has widely been reported; however, the results are inconsistent. Here, we selected three commonly studied TP53 polymorphisms: codon 72 Arg > Pro, IVS3 16 bp Del/Ins, and IVS6 + 62A > G to explore their association with breast cancer risk by meta-analysis of published case-control studies. The results showed that codon 72 was not associated with breast cancer risk among 37 combined case-control studies (23,567 cases and 25,995 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 47 publications
(43 reference statements)
5
51
5
Order By: Relevance
“…In this aspect, it is of note that some contradictions in the abovementioned meta-analyses could be due to age-related effects of TP53 germline variations. For example, breast cancer is one of a few diseases for which TP53 rs1042522 polymorphism raises many questions Hu et al, 2010b;Lu et al, 2011b;Ma et al, 2011;Peng et al, 2011;Sergentanis and Economopoulos, 2010b;The Breast Cancer Association Consortium, 2006;Zhang et al, 2010b;Zhuo et al, 2009a). According to our data, the C allele contributes to high breast cancer risk in the premenopausal period , whereas a combination of rs1042522, rs17878362, and rs1625895 major genotypes often occurs in postmenopausal BC (Perel'muter et al, 2008).…”
Section: Tp53 Polymorphismsmentioning
confidence: 76%
See 3 more Smart Citations
“…In this aspect, it is of note that some contradictions in the abovementioned meta-analyses could be due to age-related effects of TP53 germline variations. For example, breast cancer is one of a few diseases for which TP53 rs1042522 polymorphism raises many questions Hu et al, 2010b;Lu et al, 2011b;Ma et al, 2011;Peng et al, 2011;Sergentanis and Economopoulos, 2010b;The Breast Cancer Association Consortium, 2006;Zhang et al, 2010b;Zhuo et al, 2009a). According to our data, the C allele contributes to high breast cancer risk in the premenopausal period , whereas a combination of rs1042522, rs17878362, and rs1625895 major genotypes often occurs in postmenopausal BC (Perel'muter et al, 2008).…”
Section: Tp53 Polymorphismsmentioning
confidence: 76%
“…No significant contribution of TP53 rs1042522 polymorphism to oral cancer has been reported (Zhuo et al, 2009c). A high heterogeneity of results was observed in breast Hu et al, 2010b;Lu et al, 2011b;Ma et al, 2011;Peng et al, 2011;Sergentanis and Economopoulos, 2010b;The Breast Cancer Association Consortium, 2006;Zhang et al, 2010b;Zhuo et al, 2009a), colon and rectum (Dahabreh et al, 2010;Liu et al, 2011;Tang et al, 2010;Wang et al, 2010b) cancers. Though still not quite clear, cancer of the ovary (Schildkraut et al, 2009;Zhang et al, 2008), endometrium (Francisco et al, 2010;Jiang et al, 2010b), stomach (Francisco et al, 2010;Gao et al, 2009;Liu et al, 2011), bladder (Jiang et al, 2010a;Li et al, 2010), prostate Zhang et al, 2011b;Zhu et al, 2011), and skin (Francisco et al, 2010;Jiang et al, 2011) appear to be affected.…”
Section: Tp53 Polymorphisms: the Cancer Predisposing Valuementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the most recent meta-analysis indicated that the codon 72 polymorphism may not be associated with breast cancer risk in a Caucasian population. However, previous meta-analyses concerning the p53 codon 72 polymorphism also revealed conflicting results (23)(24)(25)(26). The precise reasons for this discrepancy remained to be elucidated (8,11).…”
Section: Discussionmentioning
confidence: 98%